Study of the Antioxidant Property and Xanthine Oxidase Inhibitory Activity of Various Extracts from the Algerian Medicinal Plant Paronychia argentea L. - Adjadj, Moufida; Djarmouni, Meriem (Pharmacognosy Communications)
Introduction: Paronychia argentea L. is used in traditional medicine to treat various diseases in Algeria especially kidney stones. This study was focused on the antioxidant and xanthine oxidase inhibitory activities of these plant extracts. Methods: The different extracts were prepared using solvents of increasing polarity, and their total polyphenols and flavonoids contents were determined using spectrophotomet ric methods. The anti- oxidant activities of Paronychia argentea extracts (PAE) were assessed by their inhibitory effect on xanthine oxidase (XO) and their scavenger ability on superoxide radical (O2 •-) generated by this enzyme. Results: The analysis PAE showed that ethyl-acetate extract (EaE) has the highest concentration of total phenolics and flavonoids compared with the chloroform extract (ChE) and the crude extract (CE). Results revealed that all PAE were effective in both XO inhibiting and superoxide radical scavenging, with the following order for the two assays: ChE > EaE > CE. Conclusion: This study provided evidence that PAE had interesting antioxidant potential which was con- firmed using two enzymatic methods. Therefore, this plant could be used to treat gout and lot of diseases, where inhibition of XO and scavenging of superoxide radical are necessary.
Keywords: Flavonoids; Oxidative stress; Paronychia argentea L; Superoxide anion radical; Traditional medicine; Xanthine oxidase.